Decreased expression of interferon‐stimulated genes in B cells of patients with chronic hepatitis C during interferon‐free therapy potentially suggests the eradication of hepatitis C virus in the B cells: A cohort study. Issue 3 (15th July 2020) - Arai, Jun; Ito, Takayoshi; Shimozuma, Yuu; Uchikoshi, Manabu; Nakajima, Yoko; Sakaki, Masashi; Uozumi, Shojiro; Kajiwara, Atsushi; Sugiura, Ikuya; Otoyama, Yumi; Nozawa, Hisako; Kurihara, Toshikazu; et al.
Abstract: Aims: Hepatitis C virus (HCV) infection is monitored by the host innate immunity that includes the endogenous interferon (IFN), which up‐regulates IFN‐stimulated genes (ISGs). HCV is both hepatotropic and lymphotropic, but HCV replication in lymphoid cells is a controversial issue. Here, we analyzed the mRNA levels of the ISGs in B cells of HCV‐infected patients during antiviral therapy and investigated the effects of viral eradication. Methods: One hundred and eighty‐one patients with chronic hepatitis C and 26 healthy volunteers were enrolled in this study. Levels of HCV RNA and mRNA of ISGs in B cells isolated from the patients were monitored before, during, and after antiviral therapy. Results: HCV RNA was detected in B cells of 133/175 (76.0%) patients who achieved sustained virologic response (SVR) before therapy was started. The positive ratio of HCV RNA in B cells was higher in patients with genotype 1 and the non‐major genotype of interleukin 28B. HCV RNA in B cells of most patients disappeared 1 week after antiviral therapy was started. The baseline expression of ISG mRNA was significantly higher in the patients than in the healthy volunteers. Levels of ISG mRNA were increased and remained high throughout the IFN‐based therapy. In contrast, levels of ISG mRNA in patients who achieved SVR were significantly decreased 1 week after the IFN‐free therapy was started and remained low during the therapy. Conclusions: These results suggested that IFN‐free therapy potentially eradicated HCV in the B cells, leading to the down‐regulation of endogenous ISGs. The level of ISG mRNA could be used as a marker for viral eradication in B cells.